Effects of garlic supplementation on blood pressure - Mahdaviroshan, Marjan; Nasrollahzadeh, Javad; Khodadadi, Elham (Archives of Advances in Biosciences, 2013)
Hypertension is one of the major risk factor for cardiovascular morbidity and mortality. One of primary management of hypertension include dietary changes which could incorporate dietary supplementation ,also use of non pharmacological treatment options is high in patients with high blood pressure .Garlic has played an important dietary as well as medicinal role in human history and it has been on the top ten lists of herbal sales among people. For evaluating the effect of garlic on blood pressure ,we reviewed clinical trials published from 1982 until 2013 by searching in informative bank such as PubMed، Ovid، Elsevier Science , Google Scholar with keywords garlic , blood pressure, hypertension and herbal supplement. The result of this review article showed that several clinical trials have suggested garlic lowers systolic and or diastolic blood pressure and has beneficial effect in controlling hypertension, but negative results also have been obtained in some of trials .Blood pressure reducing properties of garlic have been linked to its hydrogen sulphide production and allicin content , liberated from alliin and the enzyme alliinase. large scale trials are needed to investigate whether standardized garlic preparations could provide a safe alternative or complementary treatment option for hypertension in clinical practice.